De Novo Sequencing and Characterization of the Transcriptome of Dwarf Polish Wheat (Triticum polonicum L.) - Yi Wang; Chao Wang; Xiaolu Wang; Fan Peng; Ruijiao Wang; Yulin Jiang; Jian Zeng; Xing Fan; Houyang Kang; Lina Sha; Haiqin Zhang; Xue Xiao; et al. (International Journal of Genomics)
Construction as well as characterization of a polish wheat transcriptome is a crucial step to study useful traits of polish wheat. In this study, a transcriptome, including 76,014 unigenes, was assembled from dwarf polish wheat (DPW) roots, stems, and leaves using the software of Trinity. Among these unigenes, 61,748 (81.23%) unigenes were functionally annotated in public databases and classified into differentially functional types. Aligning this transcriptome against draft wheat genome released by the International Wheat Genome Sequencing Consortium (IWGSC), 57,331 (75.42%) unigenes, including 26,122 AB-specific and 2,622 D-specific unigenes, were mapped on A, B, and/or D genomes. Compared with the transcriptome of T. turgidum, 56,343 unigenes were matched with 103,327 unigenes of T. turgidum. Compared with the genomes of rice and barley, 14,404 and 7,007 unigenes were matched with 14,608 genes of barley and 7,708 genes of rice, respectively. On the other hand, 2,148, 1,611, and 2,707 unigenes were expressed specifically in roots, stems, and leaves, respectively. Finally, 5,531 SSR sequences were observed from 4,531 unigenes, and 518 primer pairs were designed.